Pengembangan Media Pembelajaran Interaktif Berbantuan Genially pada Materi Teks Eksplanasi untuk Meningkatkan Higher Order Thinking Skills (HOTS) Siswa Kelas XI Sekolah Menengah Atas PAB 9 Patumbak - Tri Ayu Amelia; Liesna Andryani; Rita Rita (Education & Learning, 2026)
This study aimed to develop interactive learning media assisted by Genially for explanatory text material to enhance the Higher Order Thinking Skills (HOTS) of grade XI students at SMA PAB 9 Patumbak. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The population involved 62 students from classes XI MIA and XI IS, while the sample included 33 students from class XI MIA and 29 students from class XI IS. Data were collected through questionnaires, observations, interviews, and achievement tests. Validation results from material experts indicated that the developed media was categorized as “Highly Feasible,” with an average score exceeding 90%. Similarly, validation from media experts obtained a score of 92%, also categorized as “Highly Feasible.” The effectiveness of the media was evaluated through learning mastery levels, with students’ outcomes in classes XI MIA and XI IS achieving an average mastery level of 88%. The overall effectiveness score of the media reached 71%, which falls under the “Effective” category, confirming that Genially-assisted interactive media can be appropriately used in teaching explanatory texts to support students’ higher-order thinking skills